Multiple-layered anti-counterfeit labels - Koh, Derrick (2015)
Shape memory polymers or SMPs are polymers whose which possess the ability to remember the original shape they were formed in. SMPs can exist in various states, changing from very elastic to rigid and back to very elastic when exposed to various external stimuli such as thermal, photo, or chemical stimuli. [1,2] In this report, the shape memory effect of Ethylene-vinyl acetate, also known as EVA, is investigated under a controlled environment using a series of repeatable experiments. EVA is a soft and flexible polymer with almost elastomeric properties. It can be worked with in similar methods as other thermoplastics. It is highly transparent with a glossy finish, resistant to ultraviolet radiation, has good low-temperature toughness and is highly elastic. Common uses include electrical insulation and a substitute for natural rubber in some applications. The main objective of this project is to investigate the temperatures at which EVA retains its shape memory properties. This is done by transferring two separate patterns of a coin to one side of the EVA specimen at different temperatures via constant pressure compression. Subsequently, the specimen is heated up to a temperature slightly higher than the compression temperature and the results are observed. The level of recovery and the compression and heating temperatures are recorded and analyzed.